Radiologic-Pathologic Correlation of Tumor Thickness and Its Prognostic Importance in Squamous Cell Carcinoma of the Oral Cavity: Implications for the Eighth Edition Tumor, Node, Metastasis Classification - Weimar, E.A.M.; Huang, S.H.; Lu, L.; O'Sullivan, B.; Perez-Ordonez, B.; Weinreb, I.; Hope, A.; Tong, L.; Goldstein, D.; Irish, J.; de Almeida, J.R.; Bratman, S.; et al. (American Journal of Neuroradiology, 2018)
BACKGROUND AND PURPOSE: Addressing the performance of an imaging-based parameter compared to a “gold standard” pathologic measurement is essential to achieve accurate clinical T-classification. Our aim was to determine the radiologic-pathologic tumor thickness correlation and its prognostic value in oral squamous cell carcinoma.MATERIALS AND METHODS: All pathologic T1–T3 (seventh edition of the Cancer Staging Manual of the American Joint Committee on Cancer) oral squamous cell carcinomas diagnosed between 2010 and 2015 were reviewed. Radiologic tumor thickness was measured on preoperative CT or MR imaging blinded to pathology. The radiologic-pathologic tumor thickness correlation was calculated. The impact of the imaging-to-surgery time interval and imaging technique on the correlation was explored. Intra-/interrater reliability on radiologic tumor thickness was calculated. The correlation of radiologic-versus-pathologic tumor thickness and its performance as the seventh edition T-category modifier was evaluated. Multivariable analysis assessed the prognostic value of the radiologic tumor thickness for overall survival adjusted for age, seventh edition T-category, and performance status.RESULTS: For 354 consecutive patients, the radiologic-pathologic tumor thickness correlation was similar for the image-to-surgery interval of ≤4.0 weeks (ρ = 0.76) versus 4–8 weeks (ρ = 0.80) but lower in those with more than an 8-week interval (ρ = 0.62). CT and MR imaging had similar correlations (0.76 and 0.80). Intrarater and interrater reliability was excellent (0.88 and 0.84). Excluding 19 cases with an imaging-to-surgery interval of >8 weeks, 335 patients were eligible for further analysis. The radiologic-pathologic tumor thickness correlation was 0.78. The accuracy for upstaging the T-classification based on radiologic tumor thickness was 83% for pathologic T1 and 74% for pathologic T2 tumors. Multivariable analysis confirmed the prognostic value of radiologic tumor thickness (hazard ratio = 1.5, P = .02) for overall survival.CONCLUSIONS: This study demonstrates a good radiologic-pathologic tumor thickness correlation. Intrarater and interrater reliability for radiologic tumor thickness was excellent. Radiologically thicker tumor was predictive of inferior survival.DOIdepth of invasionHRhazard ratioOSoverall survivalOSCCoral cavity squamous cell carcinomapDOIpathologic depth of invasionpTTpathologic tumor thicknessrDOIradiologic depth of invasionrTTradiologic tumor thicknessTNMtumor, node, metastasisTTtumor thickness